The Role of Legal Aid Station in Legal Aid Services in District Courts Gorontalo City - Irawati Salim Ismail (Universitas Negeri Gorontalo, 2023)
This study aims to find out how Legal Aid Services are provided by the Legal Aid Station at the Gorontalo City District Court and the obstacles in Legal Aid Services by Legal Aid Station at the Gorontalo City District Court. This type of research is Empirical Research with a descriptive approach. The results of the study show that Legal Aid Services by the Gorontalo District Court Legal Aid Station are not yet fully effective. Many people do not know about the existence of Legal Aid Station because of a lack of socialization in the community, more cases are handled and almost all of them are appointments of judges, the location of the Legal Aid Station is less strategic, lack of communication between the Legal Aid Station and the Court, the number of human resources is not proportional to the number of cases, as well as income that is disproportionate to expenses, especially civil cases. But in this case, the services in the field of providing information, consulting, and making legal documents are going well. The Legal Aid Station of the Gorontalo District Court needs to provide education in the form of outreach to the public as well as a thorough evaluation of legal services for the less fortunate.